PERSONALITY OF NORA REFLECTED IN HENRIK IBSEN A DOLL'SHOUSE PLAY (1879): A PSYCHOANALYTIC APPROACH - Setyawan, Dedy, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S. M. Hum (2016)
SUMMARY DEDY SETYAWAN. A320110149. PERSONALITY OF NORA REFLECTED IN HENRIK IBSEN A DOLL'S HOUSE PLAY (1879): PSYCHOANALYTIC APPROACH. RESEARCH PAPER.SCHOOL OF TEACHER TRAINING AND EDUCATION, MUHAMMADIYAH UNIVERSITY OF SURAKARTA. MARCH, 2016. The problem of this study is "How is the the personality of Nora reflected in Henrik Ibsen's A Doll's House play?". The objective of this study to analyze A Doll's House based on Structural analysis and the to analyze A Doll's House play based on Psychoanalytic perspective. The researcher employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source is about The primary data sources is the textplay itself. Then, the secondary data sources are from other sources such as essay, articles, biography of Henrik Ibsen, Internet and other relevant information. The method of data collection is library research and the technique of data collection is descriptive technique. Based on the anaylisis, the researcher gets some conclusions. Nora is a independent woman.In this drama, the idea implied that presents, which in its development has a duality of meaning so inviting controversial. Strength and independence that can be shown a woman, who in the end is shown by Nora and this is it personalities of ora. A principle that in terms of decision making and judgment, the opinion of a woman in this case the wife also must be heard. Man and women do have the nature of each, but doesn't mean that the woman was a " puppet", friends "play", which do not have own their self. The three words Id, Ego and Superego will be used in the Nora's structure of personality. Keywords: Psychoanalytic, A Doll's House, Personality.